1979
DOI: 10.3758/bf03199881
|View full text |Cite
|
Sign up to set email alerts
|

A conjoint measurement approach to color harmony

Abstract: The aim of this study was to find a rule in color harmony that could reveal the mutual influences of the three basic harmonies, those of hue, lightness, and saturation. One hundred and four color pairs were judged for harmony by five subjects five times. The results were analyzed by the conjoint measurement algorithm of . It was concluded that there is an interaction between saturation harmony and hue and lightness harmony together, and an additivity between hue harmony and lightness harmony. This implies the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Helson and Lansford 's (1970) overall conclusion was that color harmony is not easily predicted and depends on the interaction of the spectral characteristics of illumination source, background color, and the hue, brightness, and saturation of the object color. Their conclusion was reinforced in a later study conducted by Pieters (1979) was a function of three separate "harmonies," each related to one of the basic parameters. The function, which was derived by using a conjoint measurement algorithm, was expressed as a composition rule consisting of a distributive relationship between saturation harmony and the sum of hue harmony and brightness harmony.…”
mentioning
confidence: 90%
“…Helson and Lansford 's (1970) overall conclusion was that color harmony is not easily predicted and depends on the interaction of the spectral characteristics of illumination source, background color, and the hue, brightness, and saturation of the object color. Their conclusion was reinforced in a later study conducted by Pieters (1979) was a function of three separate "harmonies," each related to one of the basic parameters. The function, which was derived by using a conjoint measurement algorithm, was expressed as a composition rule consisting of a distributive relationship between saturation harmony and the sum of hue harmony and brightness harmony.…”
mentioning
confidence: 90%
“…They only revealed the existence of the principles. In addition, more researchers avoid the composition factors, because they usually focus on color per se . This reveals the authors' awareness of the interference from image composition with these counter evidences.…”
Section: Related Workmentioning
confidence: 99%
“…Burchett classified color harmony attributes into eight categories: area, association, attitude, configuration, interaction, order, similarity, and tone . Pieters defined the measurement of color harmony as; color harmony = saturation harmony × (hue harmony + lightness harmony) . Polzella and Montgomery's experiment suggested that harmonious color combinations involve colors of similar brightness or similar hue .…”
Section: Related Workmentioning
confidence: 99%
“…8 Pieters defined the measurement of color harmony as; color harmony 5 saturation harmony 3 (hue harmony 1 lightness harmony). 9 Polzella and Montgomery's experiment suggested that harmonious color combinations involve colors of similar brightness or similar hue. 10 Hård proposed a theoretical model of color combination, in which some attributes are related to harmony concept.…”
Section: Related Workmentioning
confidence: 99%